Multilayer stacked low-temperature-reduced graphene oxide films : preparation, characterization, and application in polymer memory devices - Liu, Juqing (2012)
Highly reduced graphene oxide (rGO) films are fabricated by combining reduction with smeared hydrazine at low temperature (e.g., 100 °C) and the multilayer stacking technique. The prepared rGO film, which has a lower sheet resistance (≈160–500 Ω sq−1) and higher conductivity (26 S cm−1) as compared to other rGO films obtained by commonly used chemical reduction methods, is fully characterized. The effective reduction can be attributed to the large “effective reduction depth” in the GO films (1.46 µm) and the high C1s/O1s ratio (8.04). By using the above approach, rGO films with a tunable thickness and sheet resistance are achieved. The obtained rGO films are used as electrodes in polymer memory devices, in a configuration of rGO/poly(3-hexylthiophene) (P3HT):phenyl-C61-butyric acid methyl ester (PCBM)/Al, which exhibit an excellent write-once-read-many-times effect and a high ON/OFF current ratio of 106.